Performance Characteristics of Lubricants in Electric and Hybrid Vehicles: A Review of Current and Future Needs - Chen, Yan; Jha, Swarn; Raut, Ajinkya; Zhang, Wenyang; Liang, Hong (Frontiers in Mechanical Engineering, 2020)
Electrical and hybrid vehicles are gaining increasing attention in recent years. The distinguished difference between electrical/hybrid vehicles from conventional ones is the intermittent on-and-off control of the internal combustion engine, while the electrical vehicles operate on electrical motors. This difference creates new requirements in lubricants with performance characteristics that are otherwise uncritical: electrical properties (such as electrical conductivity and breakdown voltage), thermal properties (thermal conductivity, specific heat, among others), in addition to fluidic performance that we have studied for decades. In this review, we discuss about lubricants for electrical and hybrid vehicles in the following aspects. Starting with a brief historic review, we gathered information about current needs and challenges in electrical and hybrid vehicles. We then compared the properties of lubricants, followed by the performance difference of those vehicles in terms of frictional performance, thermal management, and dielectric breakdown. Performance parameters are critically dependent on the properties of lubricants that are crucial for energy efficiency and reliability. This review can be used as a guidance for the future design of advanced lubricants for electrical and hybrid vehicles.